Analisis Penggunaan Aplikasi Rekam Medis Elektronik Di Puskemas Baleendah - Firmansyah, Moch Adi; Fitria, Ida Jalilah (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to examine in depth the level of effectiveness and obstacles faced in the use of RME. This study uses a qualitative descriptive approach that aims to describe in depth the effectiveness and obstacles in the use of RME at the Baleendah Health Center. Data collection techniques were carried out through triangulation, namely, observation, interviews, and documentation. The informants in this study consisted of three people, namely the Head of the Puskesmas, medical records officer, and a doctor. Overall, the results showed that the implementation of RME at the Puskesmas received full support from the management, including aspects of funding, training, technology, and regular evaluation of the problems faced. RME has become the main focus because it is considered more effective and efficient than manual systems, especially in accelerating and improving the accuracy of services. However, the implementation still encountered a number of obstacles, such as internet network disruptions in the early stages, which have now been resolved by adding devices at certain points. The limited number of IT experts is also an obstacle because it slows down the handling of technical problems. In addition, server disruptions still occur because data storage is centralized at Diskominfo along with 62 other Puskesmas in Bandung Regency, which causes delays in data access.